Corticosteroids in COVID-19: pros and cons - Bahsoun, Aymen; Fakih, Yeva; Zareef, Rana; Bitar, Fadi; Arabi, Mariam (Frontiers in Medicine, 2023)
The wide and rapid spread of the COVID-19 pandemic has placed an unanticipated burden on the global healthcare sector. This necessitated a swift response from the international community to reach a solution. Efforts were made in parallel to develop preventative and therapeutic modalities. Since then, drug repurposing has blossomed as a potentially rapid resolution and has included various agents with anti-viral and anti-inflammatory properties. Corticosteroids, being potent anti-inflammatory agents, have been placed under extensive investigation. Various trials have recorded the beneficial outcome of corticosteroids in decreasing the mortality and morbidity of COVID-19. With the high pace of escalating events, the quality and study design of clinical trials are varied. Therefore, this study aims to explore the role of corticosteroids in COVID-19 disease. It inspects the molecular, pharmacologic, and clinical proof behind this theory.